Adab-Based Character Education in KH. Hasyim Asy’ari’s Adabul ‘Alim wal Muta‘allim: Classical Pesantren Ethics and Contemporary Character Formation - Alimah Hulu (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2026)
This study examines KH. Hasyim Asy’ari’s concept of character education in Adabul ‘Alim wal Muta‘allim and analyzes its implementation at Pondok Pesantren Darul Istiqomah, Southeast Padangsidimpuan. It employs a descriptive qualitative design combining textual analysis and field research. The primary textual source is Adabul ‘Alim wal Muta‘allim, while field data were obtained through interviews, observation, and documentation. Data were analyzed through coding, categorization, thematic interpretation, and triangulation. The findings show that KH. Hasyim Asy’ari’s character education is built upon the integration of knowledge, adab, spiritual purification, and moral responsibility. Four central values are identified: purification of the heart from blameworthy traits, sincerity of intention in seeking knowledge, qana‘ah, and honoring educators in thought, speech, and action. At Pondok Pesantren Darul Istiqomah, these values are implemented through religious habituation, kitab-based learning, teacher modeling, dormitory discipline, self-reflection, and daily ethical interaction. This study concludes that KH. Hasyim Asy’ari’s educational ethics provide a relevant framework for strengthening contemporary Islamic character education by linking inner moral formation, learning motivation, disciplined communal life, teacher-student ethics, and digital moral literacy.